Imaging of the mean frequency of the ultrasonic echoes - Ziemowit Klimonda; Andrzej Nowicki (Archives of Acoustics)
A standard USG image is in fact a visualization of a distribution of the reflexion coefficients. There is an increasing interest in imaging of the different parameters, which might characterize another physical properties of a tissue. The attenuation coefficient is one of such parameters and theoretically it can be estimated using frequency shift of the RF signal. The frequency shift results from dispersive character of the attenuation in tissue and is a function of attenuation along the propagate path. In this work authors use echo’s mean frequency as an imaging modality. The results of measurement of tissue phantom using 10 MHz linear array are presented. The preliminary results are encouraging being the first attempt towards mapping of the attenuation in tissue.